Field notes contributed by Matthew Kenne, fall 1998 - Kenne, Matthewet al (1998)
Fall report of birds and locations contributed by Matthew Kenne. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed